Titanic and the making of James Cameron the inside story of the three-year adventure that rewrote motion picture history - Parisi, Paula (New York, New York Newmarket Press, 1998)
Parisi is among the few journalists whom the notoriously thin-skinned director James Cameron trusts. He granted her amazing access to Titanic, the costliest film ever made. She puts you there on that top-secret set. The opposite of the typical showbiz reporter, she is pro-Cameron. She does not dwell on the script's weaknesses, as most of the press and the Academy of Motion Picture Arts and Sciences did. But if you have any interest in how this infinitely difficult and technically innovative film was made, Parisi's is the book to read.--From amazon.com.
Includes filmographies and index.
Keywords: Titanic (Motion picture : 1997).